The importance of scale in Occupy movement protests: a case study of a local Occupy protest as a tool of communication through Public Relations and Social Media - Adi, Ana; Moloney, Kevin (Instituto de Investigación en Relaciones Públicas, 2012)
This paper explores the persuasive communications (public relations and branding through social media) of a micro Occupy event, namely a nine-day appearance of the global protest movement at Bournemouth University (BU), on the south coast of the UK. It reflects on how student and town protesters used digital and social media in comparison to the wider and more successful UK movement. It interviews the student leader, and asks questions about the role social networks like Occupii.org played in formulating communication strategies as well as how they integrated with more popular social media platforms like Facebook and Twitter. The conclusions coming from our micro case study suggest that without a supportive geographic and civic location; clear and focused messages, and robust strategic communication planning and execution, Occupy events will remain very small.
La importancia de la magnitud de las protestas del movimiento Occupy: el caso de una protesta local como instrumento de comunicación mediante las Relaciones Públicas y los Medios Sociales
Keywords: Relaciones públicas; Redes sociales; Medios de comunicación social; Occupy; Bournemouth; Social Media; Public Relations; Social Networking; Dissent PR